The Socio-Economic Impact of Waste Bank Program in Banten Province - Masruroh Masruroh; Neng Sri Nuraeni; Moch Rio Pambudi; M. Iqbal Liayong Pratama; Hendra Hendra (Jurnal Pendidikan Geografi Gea, 2022)
The Waste Bank Program is one of the programs aimed to solve waste problems and can help contribute to the community to build the community's economy. The method used is descriptive with a quantitative approach. The purpose of this study was to determine the impact of the waste bank on the socio-economic community in Banten province. Based on data analysis of the impact of the waste bank program on the socio-economic community in Banten, namely 41.5%, it can be said that the waste bank program has contributed to the socio-economic development of the community, namely the results of the Waste Bank can be used to help buy daily necessities, recycle (recycle). items that are not used, reuse items from the waste bank program and teach people to be creative by utilizing unused items (reduce). Thus the waste bank program has an impact on the socio-economic community. One of which is contributing to growing the economy, managing waste into goods of economic value, recycling waste to reduce waste that is not of value, and reusing recycled goods. The existence of the waste bank program has an economic, environmental, social and educational impact. 1) From an economic point of view, the waste bank provides a role like banks in general, namely there is a process of saving from the acquisition of waste that has been weighed in the form of waste savings, buying and selling waste. 2) Seen from the environmental perspective, the impact of the waste bank is very beneficial for the local community, because the existence of a waste bank can reduce the volume of waste in the community's living environment and final disposal site. 3) Seen from education, the Waste Bank manager teaches customers the importance of waste that can be managed, has economic value by making crafts and recycling unused waste.